New species and new records of Clavariaceae (Agaricales) from Brazil - Furtado, Ariadne N. M.; Daniëls, Pablo P.; Neves, Maria Alice (Phytotaxa, 2016)
Fourteen species in three genera of Clavariaceae from the Atlantic Forest of Brazil are described (six Clavaria, seven Clavulinopsis and one Ramariopsis). Clavaria diverticulata, Clavulinopsis dimorphica and Clavulinopsis imperata are new species, and Clavaria gibbsiae, Clavaria fumosa and Clavulinopsis helvola are reported for the first time for the country. Illustrations of the basidiomata and the microstructures are provided for all taxa, as well as SEM images of ornamented basidiospores which occur in Clavulinopsis helvola and Ramariopsis kunzei. A key to the Clavariaceae of Brazil is also included.